Ex animo. - Derksen, Theo; Devens, Paul; Dunnewijk, Marianne; Hoet, Roy; Koning, Alexander; Palmen, Hen; Ritter, Helmet; Rozendaal, Rafaël; Schneider, Sebastian; Sijben, Ine; Stoere Binken Design; Van der Zander, Frits; et al. (Maastricht : Academie Beeldende Kunsten, 2001)
Lamers, Eric ; Ekhart, Timo ; Koenen, Angelo ; Hanssen, Jill ; Albrechts, Gijs ; Vello v. Broszy, Gaby ; Schanz, Suzanne ; Wielens, Janneke ; Pöpel, Wiebke ; Eussen, Anneke ; de Natris, Neeltje ; Larue, Danièla ; Ettarfass, Sidameth ; Eussen, Anneke ; Reyven, Roel ; Meus, Danny ; Peters, Sacha ; Trautsch, Nina
Nederlands
boek
Keywords: Maastricht